LITERATURE REVIEW: Hubungan Antara Kualitas Tidur dan Nyeri Pada Malam Hari Terhadap Penderita Tendinitis Rotator Cuff - Dinda Oktavianti, (2020)
Abstract Objective: The decreased quality of sleep is influenced by movement because after the operation the average age is 12-90 years. This study aims to examine the literature, journals, articles or research results with the topic of the Correlation Between Sleep Quality and Pain at Night Against Rotator Cuff Tendinitis Patients. Method: This method is a traditional literature review, namely a comprehensive, critical, and objective analysis relating to science or knowledge on a particular topic, which helps in identification in science or knowledge. The search for data sources on this data was obtained from literature studies that have been published through electronic databases such as Google scholar, PubMed and various other journal sites. For quality assessment and selected articles using the Scimago Journal & Country Rank (SJR).Results: After reviewing the literature on 3 articles, it was shown that there was a significant relationship between sleep quality and night pain in people with Rotator Cuff Tendinitis. Conclusion: There is a relationship between sleep quality and nighttime pain in people with rotator cuff tendinitis.